'They get a qualification at the end of it, I think': incidental workplace learning and technical education in England - Esmond, Bill [Verfasser] (My University, 2018)
"Workplace learning is increasingly central to the international lifelong learning agenda but has made limited contributions to full-time vocational education in England during the last 30 years. A more central role is envisaged within the technical education proposed by the 2016 Sainsbury Review and Post-16 Skills Plan, with access to work placements dominating discussion of policy implementation. A multicase study of workplace learning among post-16 students in England on current 'study programmes' was mapped to four of the technical routes designated by the Sainsbury Review and Skills Plan, using documentary, observation and interview data. The study drew on theorisation of the workplace as the site of situated or incidental learning, whilst noting that its opportunities are differentially allocated according to organisational or personal differences, in ways that have particular implications for young people on placements. Whilst access to more advanced learning opportunities was secured through planned, collaborative approaches, reliance on incidental learning offered more routinised experiences to students less prepared for autonomous learning. The study indicates that questions of access, knowledge and pedagogy remain to be addressed if plans for 'technical education' in England are to provide meaningful learning opportunities and support transitions to fulfilling work." (authors' abstract; BIBB-Doku)
Keywords: P 2.3 Auszubildende; S 1.6 Non-formale Qualifizierung; Lernen am Arbeitsplatz; On-the-job training; Anlernung; Auszubildender; Technische Bildung; England